2013
DOI: 10.1179/1743286312y.0000000022
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of shaft lining stability at deep mine

Abstract: During the last thirty years, the Boulby Potash Mine has replaced the concrete shaft linings in sections of both shafts on two occasions following progressive deterioration. A third replacement lining is now under construction in the man shaft. This paper reports the results of two-dimensional (2D) and three-dimensional (3D) numerical modelling of the shaft linings and their surrounding strata. The numerical modelling, using FLAC 2D and FLAC 3D has considered the detrimental effect to lining stability of a wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Numerical modelling can capture more of the complex material behaviour and problem geometries than simple analytical tools, as well as the soil/rock-shaft interactions that take place, most notably due to local mining activities. For example, Jia et al [4] presented a numerical study of deep mine and identified the cause and mechanisms of failure of the shaft linings in the affected zone. Mendez et al [5] developed a numerical model to examine the effect of the shaft lining-soil interaction on shaft pressures and concluded that neglecting the interaction between the shaft and soil, as assumed by most continuum models, leads to higher values of horizontal pressure.…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%
“…Numerical modelling can capture more of the complex material behaviour and problem geometries than simple analytical tools, as well as the soil/rock-shaft interactions that take place, most notably due to local mining activities. For example, Jia et al [4] presented a numerical study of deep mine and identified the cause and mechanisms of failure of the shaft linings in the affected zone. Mendez et al [5] developed a numerical model to examine the effect of the shaft lining-soil interaction on shaft pressures and concluded that neglecting the interaction between the shaft and soil, as assumed by most continuum models, leads to higher values of horizontal pressure.…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%
“…These shafts pose a serious health and safety issue to the general public. Various research projects have been undertaken relating to the behaviour of mine shafts, including Burke and James (1990), Erasmus et al (2001), Güler (2013), Jia et al (2013), Jia (2010, Jiang and Liu (2010), Lade et al (1981), Ortlepp et al (2008) and Ortlepp (1974). The stiffness and strength of shaft linings inevitably decreases with time due to various reasons, including weathering effects, often in harsh acidic mine water.…”
Section: Introductionmentioning
confidence: 98%
“…For example, the authors (Konstantinova, S. A., Chernopazov, S. A., 2006) give an example of calculating the shaft support loads using the finite element method. (Jia Yudan, 2010;Jia, Y. D. et al, 2013) discussed the method of calculating vertical shaft lining by means of numerical modelling. Also, in their work, they described a study where the stress state of a concrete lining of a vertical shaft located in salt formations was predicted by taking into account the time factor.…”
Section: Introductionmentioning
confidence: 99%